UNIVERSAL ALGORITHMIC PROGRAMMING LANGUAGE OF MICROCONTROLLERS - Krischuk, V. N.; Malyi, A. Yu.; Voropai, A. Yu. (Radio Electronics, Computer Science, Control, 2024)
The existing methods of creation of algorithmic languages of programming are investigated. The universal programming language of microcontrollers that allows to translate the program from one microcontroller to another and also to set common algorithm of the program at work with any kind of microcontrollers is developed.